Antifungal Activities and Phytochemical Screening of Seeds, Leaves and Callus (hypocotyls and cotyledons ) Extracts of Jatropha curcas L. - ElNour, Mawahib E . M.; M . A, Magda; Ezzdeen, Lana T. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The research was under taken to investigate the antifungal activity of seeds , leaves and callus extracts of Jatropha curcas L. , using methanol and petroleum ether solvents. Callus was induced from hypocotyls and cotyledons explants in MS medium supplemented with combination of 2.0 mg/l of different auxin (2, 4-D or NAA) + 0.5 mg/l Kinetin or 0.1 BAP. Antifungal activities of extracts obtained were tested against standard fungal, Aspergillus niger (ATCC 9763), Aspergillus flavus (ATCC 9763), Aspergillus fumigatus and Candida albicans (ATCC7596). The petroleum ether extract of hypocotyls callus at concentration100mg/l gave the highest zone inhibition (18.2 ±0.3) and (18.0±0.3)mm against Candida albicans and Aspergillus fumigatus respectively, at the same time the petroleum ether extracts of hypocotyls callus at concentration 10mg/l showed high activity (16.3±0.4) mm against Candida albicans. The methanolic extracts of hypocotyls callus showed high inhibition(16.8±0.4) mm against Aspergillus fumigatus and moderate inhibition zone against Candida albicans(14.3 ±0.3), at concentration100mg/l . The results showed that methanolic callus (hypocotyls) extract gave higher inhibition zone than cotyledons callus extract. The petroleum ether extracts of seeds and leaves were ineffective against all fungi tested in this study. Aspergillus niger (ATCC 9763)and Aspergillus flavus are more resistant to all extracts of different parts of Jatropha curcas , when compared to other fungi. The concentration 100mg/l of all extracts gave more antifungal activities than the concentration 10mg/l of the extracts. The paper disc diffusion method was used to assess the in vitro testing of extracts for antifungal activity. Phytochemical screening for seeds, leaves and callus extracts indicated the presence of various secondary metabolites like flavonoids, steroids , alkaloids, tannins, sapoins , phenolic compoud and terpenoids.